Profit Comparison of Fertilized Egg Production and Consumption in Laying Hens in Gondangrejo District, Karanganyar - Abdul Hakim; Adib Norma Respati; Putri Awaliya Dughita; Fachmi Apriyanto (Journal of Livestock Science and Production, 2020)
This study aims to compare the profit of fertilized egg production and consumption in layer breeders in Gondangrejo District, Karanganyar Regency. Data was collected at layer chicken farmers in Gondangrejo District, Karanganyar Regency. The study was conducted from October to December 2019. Data were collected using a questionnaire. The method of data collection is done by purposive sampling. Purposive sampling is the taking of data by giving certain considerations or giving conditions to the samples taken. The parameters observed were chicken population, average egg production, percentage of fertilized eggs, percentage of damaged eggs, and percentage of empty eggs. The selling price of Rp. 20,000.00 / kg of consumption eggs, the selling price of fertilized eggs Rp. 2,200.00 / item and the price of empty eggs (after candling 4 days of hatching) Rp. 10,000.00 / kg or half of the price of normal consumption eggs. Respondent B had the largest difference in sales price among all respondents, namely Rp.49,754,585.00 because it had the largest layer of livestock population and the average egg production. Multiple regression analysis obtained Y = 18,479,449-30,251 X1 + 46,389 X2. Production of fertilized eggs and eggs together has a positive influence on the profitability of selling fertile eggs. The conclusion of this study is fertile egg production provides optimal profit when egg production and egg fertility are high.Keywords: Prices of fertilized eggs, egg production, fertilized egg production, coefficient of determination